Impact of Cytoreductive Surgery with Hyperthermic Intraperitoneal Chemotherapy in the treatment of Gastric Cancer with Peritoneal Carcinomatosis: a Systematic Review and Meta-Analysis - Mariana Rafaela da Fonte Martins (2022)
Background: Despite promising results, the effectiveness of cytoreduction surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with gastric cancer with peritoneal carcinomatosis (GCCP) has not been systematically evaluated. The aim of this systematic review is to compare the survival and risk of recurrence between CRS+HIPEC versus CRS alone in CGCP. Methods: A systematic review was performed in Medline and Web of Science according to the PRISMA Guidelines. Primary studies with patients with CGCP older than 18 years were included. MINORS criteria were used to assess the quality of the studies. We performed random-effects meta-analysis of risk ratios (RR). We assessed heterogeneity using the I2 statistic. Results: Seven studies were included in the qualitative and 6 in the quantitative analysis. The survival rate (SR) after 1 year was 1.63 times higher for CRS+HIPEC than CRS (RR=1.63, 95%CI=1.02-2.62, I2=70%). The SR after 5 years was more than 3 times higher for CRS+HIPEC than CRS (RR=3.25, 95%CI=1.28-8.26, I2=8%). No significant differences between CRS+HIPEC and CRS related to complications were found (RR=1.06, 95%CI=0.84-1.34, I2=0%). The risk of peritoneal recurrence was significantly lower for CRS+HIPEC than for CRS (RR=0.23, 95%CI=0.11-0.48, I2=40%). The results may be associated with some information or indication bias. Conclusions: Results should be analysed cautiously due to the detected heterogeneity and the limitations of included studies. However, treatment with CRS+HIPEC seems to increase the survival of patients with CGCP, more than treatment with CRS alone, decrease the risk of peritoneal recurrence, and not be associated with more postoperative complications.